Surface mass balance, sublimation and snow temperatures at Dome Fuji Station, Antarctica, in 1995 - Kameda, Takao; Azuma, Nobuhiko; Furukawa, Teruo; Ageta, Yutaka; Takahashi, Shuhei
The paper focuses on the first year-round observations of surface mass balance，sublimation and snow temperatures at Dome Fuji Station. This Station was newly established at the highest point（77°19′0l′′S，39°42′12′′E；381Om）in Queen Maud Land，Antarctica by the Japanese Antarctic Research Expedition. It was found that average surface mass balance by the stake method was ＋2．5gcm^<-2> from 25 January 1995 to 30 January 1996（370 days），of which about 95％ of the positive balance was obtained from February to the middle of October(eight and half months). Sublimation from atmosphere to snow surface (mass input：＋0．55gcm^<-2>）was predominant in winter（March to October）and sublimation from snow surface to atmosphere (mass output: -0.39gcm^<-2>) was predominant in summer (November to February)．In the annual balance，sublimation from atmosphere to snow surface (+0.16gcm^<-2>) prevailed. This corresponds to about 6％ of the annual surface mass balance. The snow temperature at 10 m depth varied from -57.0 to -57.8℃，and the annual mean 10 m snow temperature was -57.3℃. application/pdf journal article